Young Children Are More Likely to Spontaneously Attribute Mental States to Members of Their Own Group. (October 2017) - McLoughlin, Niamh; Over, Harriet
We investigated whether young children were more likely to spontaneously attribute mental states to members of their own social group than to members of an out-group. We asked 5- and 6-year-old children to describe the actions of interacting geometric shapes and manipulated whether the children believed these shapes represented their own group or another group. Children of both ages spontaneously used mental-state words more often in their description of in-group members compared with out-group members. Furthermore, 6-year-olds produced a greater diversity of mental-state terms when talking about their own social group. These effects held across two different social categories (based on gender and geographic location). This research has important implications for understanding a broad range of social phenomena, including dehumanization, intergroup bias, and theory of mind.